Measurement of triple gauge WWγ couplings at LEP2 using photonic events - BARATE, R. (Institutional Knowledge at Singapore Management University, 1998)
A study of events with photons and missing energy has been performed with the data sample obtained with the ALEPH detector at centre-of-mass energies from 161 to 184 GeV, corresponding to a total integrated luminosity of about 80 pb−1. The measured distributions are in agreement with Standard Model predictions, leading to constraints on WWγ gauge coupling parameters Δκγ and λγ. The results from the fit to the cross sections and to the energy and angular distributions of the photons are: Δκγ=0.05+1.15−1.10(stat)±0.25(syst), λγ=−0.05+1.55−1.45(stat)±0.30(syst).